Involvement of substance P in the antinociceptive effect of botulinum toxin type A: Evidence from knockout mice. (1st September 2017) - Matak, Ivica; Tékus, Valéria; Bölcskei, Kata; Lacković, Zdravko; Helyes, Zsuzsanna
Highlights: BoNT/A does not reduce pain in substance P and NK1R knockout mice. BoNT/A is ineffective in knockouts in spite of its enzyme activity in dorsal horn. We conclude that SP-NK1R transmission modulates the BoNT/A nociceptive activity. Abstract: The antinociceptive action of botulinum toxin type A (BoNT/A) has been demonstrated in behavioral animal studies and clinical settings. It was shown that this effect is associated with toxin activity in CNS, however, the mechanism is not fully understood. Substance P (SP) is one of the dominant neurotransmitters in primary afferent neurons transmitting pain and itch. Thus, here we examined association of SP-mediated transmission and BoNT/A antinociceptive action by employing gene knockouts. Antinociceptive activity of intraplantarly (i.pl.) injected BoNT/A was examined in mice lacking the gene encoding for SP/neurokinin A (tac1 −/− ) or SP-preferred receptor neurokinin 1 (tac1r −/− ), compared to control C57Bl/6 J wild type animals. BoNT/A action was assessed in inflammatory pain induced by formalin and CFA, and neuropathic pain induced by partial sciatic nerve ligation. BoNT/A activity in CNS was examined by c-Fos and BoNT/A-cleaved SNAP-25 immunohistochemistry. In wild type mice, acute (formalin-evoked) and chronic pain (neuropathic and inflammatory) was reduced by peripherally injected BoNT/A. In tac1 −/− and tac1r −/− knockout mice, BoNT/A exerted no analgesic effect. In control animals BoNT/A reduced the formalin-evoked c-Fos expression in lumbar dorsal horn, while in knockout mice the c-Fos expression was not reduced. After peripheral toxin injection, cleaved SNAP-25 occurred in lumbar dorsal horn in all animal genotypes. BoNT/A antinociceptive activity is absent in animals lacking the SP and neurokinin 1 receptor encoding genes, in spite of presence of toxin's enzymatic activity in central sensory regions. Thus, we conclude that the integrity of SP-ergic system is necessary for the antinociceptive activity of BoNT/A.